2022
DOI: 10.3390/insects13040360
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Near-Infrared Spectroscopy (NIRS) for Evaluation of Aedes aegypti Population Age Structure

Abstract: Given that older Aedes aegypti (L.) mosquitoes typically pose the greatest risk of pathogen transmission, the capacity to age grade wild Ae. aegypti mosquito populations would be a valuable tool in monitoring the potential risk of arboviral transmission. Here, we compared the effectiveness of near-infrared spectroscopy (NIRS) to age grade field-collected Ae. aegypti with two alternative techniques—parity analysis and transcript abundance of the age-associated gene SCP1. Using lab-reared mosquitoes of known age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The relationship between transcript abundance of SCP and chronological age was not significantly different between fed and unfed mosquitoes. This method for obtaining a continuous measure of age was used in a recent study which compared the accuracy of this age-grading method to that of using near-infrared spectroscopy (NIRS) and found that NIRS was not as reliable as SCP-1 transcript expression [ 67 ]. The R code used to generate this continuous age variable can be found in the https://github.com/ejeffreygutierrez/Predicting-Aedes-age .…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between transcript abundance of SCP and chronological age was not significantly different between fed and unfed mosquitoes. This method for obtaining a continuous measure of age was used in a recent study which compared the accuracy of this age-grading method to that of using near-infrared spectroscopy (NIRS) and found that NIRS was not as reliable as SCP-1 transcript expression [ 67 ]. The R code used to generate this continuous age variable can be found in the https://github.com/ejeffreygutierrez/Predicting-Aedes-age .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, NIR has been suggested as a useful tool to monitor the changes in age structure over time in an Ae. aegypti (Linnaeus) population, an aspect of key relevance for determining the effectiveness of vector control [ 185 ].…”
Section: Autofluorescence In Dipteramentioning
confidence: 99%
“…Krajacich et al (2017) reported that the highest classification rate of an independent cohort of wild-caught Anopheles gambiae larvae reared to set ages was only 69.6%. Recently, Ong et al (2020) concluded that they were unable to predict age of field-derived Aedes albopictus mosquitoes, and Joy et al (2022) did not find NIR to be suitable for predicting the precise age of individual field-collected Ae. aegypti mosquitoes.…”
Section: Introductionmentioning
confidence: 99%